Cariprazine (RGH-188), a potent D3/D2 dopamine receptor partial agonist, binds to dopamine D3 receptors in vivo and shows antipsychotic-like and procognitive effects in rodents - Gyertyán, István; Kiss, Béla; Sághy, Katalin; Laszy, Judit; Szabó, Györgyi; Szabados, Tamás; Gémesi, Larisza I.; Pásztor, Gabriella; Zájer-Balázs, Mária; Kapás, Margit; Csongor, Éva Ágai; Domány, György; et al. (Neurochemistry international, 2011)
We investigated the in vivo effects of orally administered cariprazine (RGH-188; trans-N-{4-[2-[4-(2,3-dichlorophenyl)-piperazin-1-yl]-ethyl]-cyclohexyl}-N',N'-dimethyl-urea), a D(3)/D(2) dopamine receptor partial agonist with ∼10-fold preference for the D(3) receptor. Oral bioavailability of cariprazine at a dose of 1mg/kg in rats was 52% with peak plasma concentrations of 91ng/mL. Cariprazine 10mg/kg had good blood-brain barrier penetration, with a brain/plasma AUC ratio of 7.6:1. In rats, cariprazine showed dose-dependent in vivo displacement of [(3)H](+)-PHNO, a dopamine D(3) receptor-preferring radiotracer, in the D(3) receptor-rich region of cerebellar lobules 9 and 10. Its potent inhibition of apomorphine-induced climbing in mice (ED(50)=0.27mg/kg) was sustained for 8h. Cariprazine blocked amphetamine-induced hyperactivity (ED(50)=0.12mg/kg) and conditioned avoidance response (CAR) (ED(50)=0.84mg/kg) in rats, and inhibited the locomotor-stimulating effects of the noncompetitive NMDA antagonists MK-801 (ED(50)=0.049mg/kg) and phencyclidine (ED(50)=0.09mg/kg) in mice and rats, respectively. It reduced novelty-induced motor activity of mice (ED(50)=0.11mg/kg) and rats (ED(50)=0.18mg/kg) with a maximal effect of 70% in both species. Cariprazine produced no catalepsy in rats at up to 100-fold dose of its CAR inhibitory ED(50) value. Cariprazine 0.02-0.08mg/kg significantly improved the learning performance of scopolamine-treated rats in a water-labyrinth learning paradigm. Though risperidone, olanzapine, and aripiprazole showed antipsychotic-like activity in many of these assays, they were less active against phencyclidine and more cataleptogenic than cariprazine, and had no significant effect in the learning task. The distinct in vivo profile of cariprazine may be due to its higher affinity and in vivo binding to D(3) receptors versus currently marketed typical and atypical antipsychotics.